2014
DOI: 10.1177/1461444814522945
|View full text |Cite
|
Sign up to set email alerts
|

The domestication of digital games in the lives of older adults

Abstract: The current study aims to integrate the findings of previous research on the use of video games by older adults by applying the domestication framework developed in the 1990s. A qualitative study was performed with 35 participants aged between 49 and 73, who were targeted purposefully from a larger sample of 213. The analysis revealed how older adults appropriated digital games using pre-existing, public and co-constructed meanings, as well as how such meanings influence the incorporation of digital games in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 18 publications
3
47
1
5
Order By: Relevance
“…Any pleasures assumed to be elicited through game use were largely articulated within more dominant tropes in which users were constructed as concerned primarily with the worthy pursuit of cognitive health and enhancement. This finding supports studies of gaming technologies that have shown that adult game use might not be regarded as age-appropriate (De Schutter et al., 2015), and hence rationalised and legitimizing in ways that reflect cultural norms of adulthood (Thornham, 2009). …”
Section: Discussionsupporting
confidence: 89%
“…Any pleasures assumed to be elicited through game use were largely articulated within more dominant tropes in which users were constructed as concerned primarily with the worthy pursuit of cognitive health and enhancement. This finding supports studies of gaming technologies that have shown that adult game use might not be regarded as age-appropriate (De Schutter et al., 2015), and hence rationalised and legitimizing in ways that reflect cultural norms of adulthood (Thornham, 2009). …”
Section: Discussionsupporting
confidence: 89%
“…In contrast to the images created by designers and what people expect, implicit methods are often more powerful than explicit methods in shaping the design. [48, p. 41], Loos [45] and Loos and Romano Bergstrom [49] argue that young male game designers may specifically tend to overlook the aspect of age-related functional limitations due to the factors mentioned in the Table above. We agree with De Schutter et al [59] that "Designers must be aware of normative age-related changes and (1) how such aspects can affect technological interaction (e.g. reduced vision and hearing, slower pace, decreased attention division skills, etc., IJsselsteijn et al [51, p. 1171…”
Section: Giving Voice To Older Adults' Capability To Play Exergamessupporting
confidence: 83%
“…The same toxicity is found when studying actively playing older adults; participants of our own qualitative research (e.g., De Schutter, Brown, and Vanden Abeele 2014;De Schutter and Malliet 2014) talked about how it was socially unacceptable for them to play games. For example, one 62-year-old female participant told us how she hid her Nintendo Gameboy when a friend came to visit, and remarked "When I play my Gameboy outside of my home I see people looking at me; they think that I have gone crazy."…”
mentioning
confidence: 54%